A Dutch Family in the Middle Colonies : 1660-1880 - Fabend, Firth Haring, 1937- (Book collections on Project MUSE., 1991)
Traces the history of the Haring family: descendants of John Pietersen Haring (fl.17th c.) and Grietje Cosyns (b.1641) who were married in 1662 in the Out-ward of Manhattan. Their descendants lived in New York and New Jersey. John and Grietje were not immigrants, but were the children of immigrants from the Netherlands. The history is prim arily description of how and under what conditions the family would have lived; includes a great deal of sociological, cultural, religiou s, and other detailed information.